Relevance of e-SERVQUAL for determining the quality of FinTech services. (5th December 2019) - Baber, Hasnan
Despite the rise of FinTech, the definition of this sector is still vague. The services offered by FinTech differ widely, but all share some commonalities. As FinTech is a growing service sector, there is a need to check the service quality offered by the different service providers. The study was conducted on Islamic banks of Malaysia and UAE which offer Fintech services to their customers. A 26-item questionnaire was used to gather data from 325 customers by strata sampling. Statistical data was analysed through various tests like reliability analysis, sample adequacy, factor analysis and regression analysis using SPSS 25.0. Shariah compliance variable was added to the e-SERVQUAL model to make it relevant for Islamic banks. This study found that Shariah compliance information, site aesthetic, efficient and reliable services, and fulfilment of promises and transaction has a significant impact on the customer satisfaction in Islamic banks for the FinTech services offered.